Meat Hygiene Practices Among Meat Sellers in Dharan Municipality of Eastern Nepal - Bhattarai, Jamuna; Badhu, A; Shah, T; Niraula, SR (Birat Journal of Health Sciences, 2017)
IntroductionEating the meat derived from animals suffering from zoonotic diseases or contaminated with meat borne bacteria cause infection or intoxication and grave danger to both the handler and consumer causing morbidity and mortality.ObjectiveThe study aims to assess the meat hygiene practices among meat sellers in Dharan City of Eastern Nepal.MethodologyA descriptive cross sectional study was carried in all meat shops registered in Dharan from December 2013 to December 2014. A total of 125 meat shops, which were registered in Dharan Municipality, Dharan Mashu Baybasashi Prabadhi Sang and Dharan Mashu Baybasashi Sangh were enrolled. Checklist and semi structured interview schedule were used to assess the hygiene practices of meat shops. Data were analyzed by using descriptive as well as inferential statistics.ResultsThis study revealed that practice of meat inspection, antemortem and post-mortem examination of animals/carcass were not seen and separate slaughterhouse was not made. Only few (19%) of the respondents had practice of washing hands before and a